The Effect Of The Idea Gardens Strategy On Productive Thinking Among First-Year Middle School Students In Biology (Journal of the College of Basic Education, 2025)
The current research aims to know “the effect of the Idea Gardens strategy on productive thinking among first-year middle school female students in biology .” To verify the researcch objective, the researcher formulated the following null hypothesis: “There is no statiistically significant difference at the leevel of significance (0.05) between the average scores of the experimental group students who study accordiing to the Ideas Gardens strategy and the average scores of the control group students who study according to the traditional method in the subject of biology.” The researcher adopted the experimental approach with partial control, as the research sample consisted of (67) female students who were selected randomly. The researcher rewarded the two research groups with variiables (chronologiical age, intelligence, previous information test). A multiple-choice test of productive thinking skills was prepared, consisting of (40) items, and its psychometric properties were verified. The test was applied and the data were statistically processed using the t-.test for the two research samples, and it reached (4.10), which is greater than the tabuilar value of (2). The results showed a statistically significant difference at the level of significance (0.05) in favour of the experimental group students who studied according to the Ideas Gardens strategy. Hence, the researcher recommended the necessity of adopting the strategy of the gardens of ideas in teaching biology for the first intermediate grade, and suggested holding training courses and workshops to train teachers on modern strategies, especially those based on the principle of constructivist theory.